2020
DOI: 10.1002/chem.202003830
|View full text |Cite
|
Sign up to set email alerts
|

Large‐Scale Synthesis of a Niche Olefin Metathesis Catalyst Bearing an Unsymmetrical N‐Heterocyclic Carbene (NHC) Ligand and its Application in a Green Pharmaceutical Context

Abstract: Al arge-scale synthesis of knownR uo lefin metathesis catalyst VII featuring an unsymmetrical N-heterocyclic carbene (NHC) ligand with one 2,5-diisopropylphenyl (DIPP) and one thiophenylmethylene N-substituent is reported. The optimised procedure does not requirec olumnc hromatography in any step and allows forp reparation of up to 0.5 kg batches of the catalystf rom simple precursors.T he application profile of the obtainedc atalystw as studied in environmentally friendly dimethyl carbonate (DMC). Although VI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 82 publications
2
12
0
Order By: Relevance
“…Green chemistry is an increasing trend not only in chemical industry but also in academia. 59 62 Despite the environmental needs and the availability of many alternative solvents such as water, 63 ethyl acetate, 64 , 65 dimethyl carbonate, 66 , 67 2-MeTHF, 68 , 69 and 4-MeTHP, 61 , 70 the usage of green solvent for olefin metathesis is relatively scarce. We therefore screened both the general-purpose Hoveyda–Grubbs second-generation catalyst ( Ru1 , see Figure 1 ) and the tagged StickyCat PF 6 ( Ru2 ) in RCM of diethyl diallylmalonate ( 1 ) used as a model substrate, in two solvent systems—DCM (not green) and EtOAc (green).…”
Section: Results and Discussionmentioning
confidence: 99%
“…Green chemistry is an increasing trend not only in chemical industry but also in academia. 59 62 Despite the environmental needs and the availability of many alternative solvents such as water, 63 ethyl acetate, 64 , 65 dimethyl carbonate, 66 , 67 2-MeTHF, 68 , 69 and 4-MeTHP, 61 , 70 the usage of green solvent for olefin metathesis is relatively scarce. We therefore screened both the general-purpose Hoveyda–Grubbs second-generation catalyst ( Ru1 , see Figure 1 ) and the tagged StickyCat PF 6 ( Ru2 ) in RCM of diethyl diallylmalonate ( 1 ) used as a model substrate, in two solvent systems—DCM (not green) and EtOAc (green).…”
Section: Results and Discussionmentioning
confidence: 99%
“…However, first, to show a perspective for a large-scale production, we undertook a half-kilogram scale synthesis of this complex which has been obtained in 15 % yield over 12 steps from commercially available and cost-efficient precursors, such as RuCl 3 , 2,6-diisopropylaniline, and salicylic aldehyde. [54] Next, we found that this complex is stable under air in non-degassed common organic solvents (DCM, toluene), as well as in so-called "green solvents" [55] such as 2-MeTHF or dimethyl carbonate (DMC) usually leading to very good results in a range of metathesis reactions. [56] What is more, high selectivity of complex Ru52 has been demonstrated in ethenolysis of ethyl oleate (27) and in a set of self-CM reactions of various terminal olefins (Scheme 10).…”
Section: A Versatile Thiophene-based Unhc Ru Catalystmentioning
confidence: 99%
“…(2-MeTHF), [58] 4-methyltetrahydropyran (4-MeTHP), [62] and dimethyl carbonate (DMC). [54] For example, a collection of polyfunctional substrates including active pharmaceutical ingredients (API), such as modafinil (46) and SUAM 1221 (47) derivatives have been successfully obtained in RCM reaction (Scheme 12a). Of note, the corresponding products 44-47 were obtained in excellent yield with only 0.4-0.5 mol % of Ru52.…”
Section: A Versatile Thiophene-based Unhc Ru Catalystmentioning
confidence: 99%
See 2 more Smart Citations